Pengaruh Job Description Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Pelni (Persero) Cabang Makassar - Ampauleng; Abdullah, Salma (Insan Cita Bongaya Research Journal, 2022)
This study aims to examine and analyze the effect of job description and workenvironment on employee performance at PT. PELNI (PERSERO) Makassar Branch. Thisstudy is to examine and analyze the effect of job description on employee performance, theeffect of the work environment on employee performance and the simultaneous influence of jobdescription and work environment on employee performance. Data collection using primarydata obtained from employees as many as 35 respondents with a saturated sampling techniquethrough a questionnaire.The results showed that the job description and work environment had a positive andsignificant effect on employee performance so that all proposed hypotheses were accepted.